Barriers and facilitators to implementing workplace health and wellbeing services in the NHS from the perspective of senior leaders and wellbeing practitioners: a qualitative study - Helen Quirk; Helen Crank; Anouska Carter; Hanna Leahy; Robert J. Copeland (BMC, 2018)
Abstract Background The National Health Service (NHS) seems appropriately placed to be an exemplar employer in providing effective and proactive workplace health and wellbeing services for its staff. However, NHS staff sickness absence costs an estimated £2.4 billion. Evidence suggests staff health and wellbeing services delivered in the NHS can improve health, productivity and sickness absence and yet the adoption of these services remains a challenge, with few examples nationally. This research aimed to explore the perceptions of NHS senior leaders and health and wellbeing practitioners regarding barriers and facilitators to implementing workplace health and wellbeing services for staff in the NHS. Methods Semi-structured interviews were conducted with NHS staff, consisting of four senior leaders, four heads of department and three health and wellbeing practitioners in one region of the UK. Interviews were transcribed verbatim and analysed using thematic analysis. Results Themes describe the experience of delivering workplace health and wellbeing services in the NHS, and barriers and facilitators to implementation from senior decision makers. Barriers to implementation of services include; a busy and pressurised environment, financial constraints and reluctance to invest in staff health and wellbeing. Barriers to staff engagement were also reported and include difficulty of access to health and wellbeing services and lack of time. Initiating services were facilitated by financial incentives, a supportive organisational structure and culture that takes a preventative, rather than reactive, approach to staff health and wellbeing. Facilitators to implementing health and wellbeing services include a coherent, strategic approach to implementation, effective communication and advertisement, being creative and innovative with resources and conducting a needs analysis and evaluation before, during and after implementation. Conclusions Barriers to the successful initiation and implementation of health and wellbeing services in the NHS are numerous and range from front-line logistical issues with implementation to high-level strategic and financial constraints. Adopting a strategic and needs-led approach to implementation and ensuring thorough staff engagement are amongst a number of factors that facilitate implementation and help overcome barriers to initiation of wellbeing programmes in the NHS. There is a need for a culture that supports staff health and wellbeing in the NHS.